WHOLE-ROCK AND ND-PB ISOTOPE GEOCHEMISTRY AND RADIOLARIAN AGES OF THE VOLCANICS FROM THE YUKSEKOVA COMPLEX (MADEN AREA, ELAZIG, E TURKEY): IMPLICATIONS FOR A LATE CRETACEOUS (SANTONIAN-CAMPANIAN) BACK-ARC BASIN IN THE SOUTHERN NEOTETHYS - Ural, Melek; Sayit, Kaan; Tekin, Ugur Kagan (Ofioliti, 2022)
The Southeast Anatolian Orogenic Belt (SAOB) is characterized by a tectonic assemblage consisting of dismembered ophiolites, subduction-related assemblages, and continental fragments. Whether the subduction-related volcanic assemblages formed in a Southern Neotethys oceanic arc-basin system (the Yuksekova Complex) or in a back-arc basin (the Maden Complex) originated after the closure of Southern Neotethys is still debated. To shed light on this matter, we focus on the Maden area, known as the type locality for the Maden Complex. The dating of radiolarian cherts associated with the volcanics from the Maden area yields Late Cretaceous (Santonian-Campanian) ages, indicating that these extrusives belong to the Yuksekova Complex. The Yuksekova volcanics are all subalkaline and mainly characterized by basalts, with subordinate andesitic varieties. The Zr-Nb-Y systematics of the Yuksekova lavas suggest that they have tapped a heterogeneous mantle source region with variable contribution from the depleted mantle. The positive eNd values of the volcanics also support the involvement of the depleted mantle. A common feature of the Yuksekova lavas is the marked depletion in Nb relative to Th and La, indicating a subduction-modified mantle source for their petrogenesis. The Pb isotope systematics, particularly the high Pb-207/Pb-206, further implies a variable slab-derived sediment input in the source of these volcanics. Overall, trace element and isotopic characteristics of the Yuksekova lavas are consistent with their generation in an oceanic back-arc basin during the Santonian-Campanian interval in the Southern Neotethys. The Yuksekova back-arc basin characterizes the westward continuum of an extensive Late Cretaceous intra-oceanic subduction system, whose remnants can be traced further to the east, toward Iran.
Keywords: Yuksekova Complex; Nd-Pb isotopes; subduction; Southern Neotethys; Elazig; Turkey